2014
DOI: 10.3354/ame01686
|View full text |Cite
|
Sign up to set email alerts
|

Exploring bacteria–diatom associations using single-cell whole genome amplification

Abstract: Diatoms are responsible for a large fraction of oceanic and freshwater biomass production and are critically important for sequestration of carbon to the deep ocean. As with most surfaces present in aquatic systems, bacteria colonize the exterior of diatom cells, and they interact with the diatom and each other. The ecology of diatoms may be better explained by conceptualizing them as composite organisms consisting of the host cell and its bacterial associates. Such associations could have collective propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 66 publications
3
23
1
Order By: Relevance
“…In contrast to our previous work on the attached bacteria of field-collected single diatom cells (Baker and Kemp, 2014), the two major phylotypes associated with Chaetoceros sp. KBDT20 were Alteromonas and Marinobacter, two genera previously reported to be associated with algal hosts including diatoms (Amin et al, 2012a, b).…”
Section: Diatom-associated Bacterial Abundance and Diversitycontrasting
confidence: 91%
See 1 more Smart Citation
“…In contrast to our previous work on the attached bacteria of field-collected single diatom cells (Baker and Kemp, 2014), the two major phylotypes associated with Chaetoceros sp. KBDT20 were Alteromonas and Marinobacter, two genera previously reported to be associated with algal hosts including diatoms (Amin et al, 2012a, b).…”
Section: Diatom-associated Bacterial Abundance and Diversitycontrasting
confidence: 91%
“…with recurrence and relative abundance of each phylotype. In our previous work, we found a maximum of 61 bacterial cells attached to a single field‐collected diatom cell (mean of 24 bacterial cells per diatom), but a maximum of 11 different bacterial OTUs co‐occurring on one diatom (Baker and Kemp, ). This may indicate that some free‐living bacteria were carried over during the original isolation.…”
Section: Resultsmentioning
confidence: 96%
“…Notably, studies addressing bacterial community assembly resulting from interactions between two microscopic players (i.e., phytoplankton and seawater bacteria) are challenging due to the microscopic scale at which they occur. The only studies to date, comparing bacterial assemblages on individual cells of congeneric diatoms obtained from natural waters, found that recovered bacterial phylotypes were extremely diverse and rarely shared across individual diatom cells [27,28], potentially supporting a lottery assembly model.…”
Section: Introductionmentioning
confidence: 99%
“…Cell sorters typically divert cells within a defined flow cytometric parameter space (i.e., defined by fluorescence and/or light scattering measurements) into a holding container; the cells within the holding container can then be analyzed further (Chisholm et al 1988a). Cell sorting has been used in combination with a variety of chemical analyses to better understand biogeochemical cycling (Fawcett et al 2011;Lomas et al 2011), to delve into interactions between bacteria and phytoplankton (Thompson et al 2012;Baker and Kemp 2014), and to investigate intra-species genetic variability (Kashtan et al 2014). With advances in single-cell genomics, transcriptomics, and cell sorting technologies, it is now possible to conduct analyses of individual sorted cells that have been isolated from cultures or environmental samples (Baker and Kemp 2014;Kashtan et al 2014;Luo et al 2014;Thrash et al 2014).…”
mentioning
confidence: 99%